Implementasi Kegiatan Finger Painting Dalam Meningkatkan Motorik Halus Pada Anak Usia 4-5 Tahun Di PAUD Anggrek VIII - Kurniasih , Samsy; Kasih , Delina; Mulyanti , Fitrah (CV. ITTC INDONESIA, 2024)
Fine motor skills are a very important motor development in early childhood. Early childhood education institutions are places where children should be provided with needs-based, step-by-step services to receive advice about their development. Background: Writing fine motor skills is carried out at the age of 4 - 5 years at PAUD ANGGREK VIII Kepa Duri Kebon Jeruk, West Jakarta. The research was carried out in 2 cycles and 10 meetings held from 3 - 7 June 2024, cycle I and Cycle II were carried out on 10 - 14 June 2024 with 10 children. The research method used is action research (classroom action research). Data collection was carried out through interviews and observations. The results of the research show that fine motor skills can be improved with finger painting activities, as evidenced by the percentage achieved in each cycle of the criteria for developing according to expectations (BSH) of 5 children or 50% in the second cycle increasing to 9 children or 90%. Based on this increase, it can be concluded that fine motor skills can be improved through finger painting activities for children aged 4 - 5 years at PAUD ANGREK VIII Kepa Duri, Kebon Jeruk, West Jakarta.